An Evidence for a Novel Antiviral Mechanism: Modulating Effects of Arg-Glc Maillard Reaction Products on the Phase Transition of Multilamellar Vesicles - Ke, Lijing; Luo, Sihao; Rao, Pingfan; Bradshaw, Jeremy P.; Sa'adedin, Farid; Rappolt, Michael; Zhou, Jianwu (Frontiers in Cell and Developmental Biology, 2021)
Maillard reaction products (MRPs) of protein, amino acids and reducing sugars from many foods and aqueous extracts of herbs are found to have various bioactivities, including antiviral effects. A hypothesis was proposed that their antiviral activity is due to the interaction with cellular membrane. Aiming to estimate the possible actions of MRPs on phospholipids bilayers, the Arg-Glc MRPs were prepared by boiling the pre-mixed solution of arginine and glucose for 60 min at 100˚C, then examined at a serial of concentrations for their effects on the phase transition of MeDOPE multilamellar vesicles (MLVs), for the first time, by using differential scanning calorimetry (DSC) and temperature-resolved small-angel X-ray scattering (SAXS). Arg-Glc MRPs inhibited the lamellar gel-liquid crystal (Lβ-Lα), lamellar liquid crystal-cubic (Lα-QII) and lamellar liquid crystal-inverted hexagonal (Lα-HII) phase transitions at the low concentration (molar ratio of lipid v.s. MRPs was 100:1 or 100:2), but promoted all the three transitions at the medium concentration (100:5). At the high concentration (10:1), the MRPs’ exhibited inhibitory effect again. The fusion peptide from simian immunodeficiency virus (SIV) induces membrane fusion by promoting the formation of non-lamellar phase, e.g. cubic (QII) phase, and inhibiting the transition to HII. Arg-Glc MRPs, at the low concentration, stabilised the lamellar structure of SIV peptide containing lipid bilayers, but facilitated the formation of non-lamellar phases at the medium concentration (100:5). The concentration-dependent activity of MRPs upon lipid phase transition indiciates a potential role in modulating some membrane-related biological events, e.g. viral membrane fusion.